Jeremiah 31:31-34: A prospect of true transformation - Terblanche, M.D. (Acta Theologica, 2021)
The theme of the transformation of reality is one of the unifying themes in Jeremiah 30-31. A past-future tension is notably present in 31:31-34, with the promise of a new covenant. This article considers the contrast between the new covenant pericope and the poetic doom oracles and the prose discourses in the book of Jeremiah. Since the book of Deuteronomy seemingly had a profound influence on the book of Jeremiah, Jeremiah 31:31-34 is also read against the background of Deuteronomy. Allusions in Jeremiah 31:31-34 to these texts are especially significant. It is argued that these allusions demonstrate that the new covenant passage attained a distinct identity by the promise of a radical transformation. In addition, the application of utopian literary theory suggests that Jeremiah’s utopian vision enflamed possibility and awakened emotional yearning for a better world.